Taxonomic and nomenclatural novelties in Marcetieae (Melastomataceae) from Colombia: A new species of Ernestia and the identity of Acisanthera goudotii - Silva, Diego Nunes Da; Murillo-Serna, Jhon S.; Hoyos-Gómez, Saúl E.; Bernal, Rodrigo; Michelangeli, Fabián A.; Braga, João Marcelo Alvarenga; Guimarães, Paulo José Fernandes (Phytotaxa, 2024)
During the development of the taxonomic treatment of Ernestia we came across a taxonomic novelty and a species for which taxonomic verification was needed from Colombia. Herein, we propose Ernestia rheophytica a new species belonging to the sensu stricto clade of the genus, and clarify the identity of Acisanthera goudotii, now treated as E. goudotii. We also clarify the status of the original material of E. goudotii and propose the lectotypification of E. ovata and its synonymization under E. goudotii. Ernestia rheophytica, as the name indicates, is a rheophytic species, a rare habit in Melastomataceae, especially in Marcetieae.